Insights into Cyberlaw and Lifestyle: Scholarly Analysis Dataset - Islam, Alif; Rosnawati, Emy; Masudin, Noor (Proceedings of The ICECRS, 2023)
This data article offers an insightful examination of scholarly articles sourced from lens.org, focusing on Cyberlaw, Cyber, Law, and Lifestyle. Employing specific keyword searches, document type filters, and subject categorization, the dataset, available in CSV and BibTeX formats via Zenodo, aims to quantify relevant journal articles, identify top affiliations, active countries, and prevalent publishers. Notably, the analysis unveils the prominence of the London School of Economics and Political Science, emphasizing data security and European Court of Justice rulings. Furthermore, a surge in publications, particularly centered on online privacy and racism, peaked in 2017. This dataset provides an essential resource for researchers, students, and organizations delving into these intersecting domains, shedding light on trends and pivotal contributors in the field. Highlight: Dominant Institution: London School of Economics and Political Science's significant presence, emphasizing data security and European Court of Justice rulings. Publication Trends: Sharp increase in articles, especially concerning online privacy and racism, peaking in 2017. Resource Utility: Valuable reference for researchers, students, and organizations interested in the intersection of Cyberlaw, Cyber, Law, and Lifestyle. Keywords: Cyberlaw, Lifestyle, Scholarly Articles, Data Analysis, London School of Economics